Studying the DNA damage response pathway in hematopoietic canine cancer cell lines, a necessary step for finding targets to generate new therapies to treat cancer in dogs - Hernández-Suárez, Beatriz; Gillespie, David A.; Dejnaka, Ewa; Kupczyk, Piotr; Obmińska-Mrukowicz, Bożena; Pawlak, Aleksandra (Frontiers in Veterinary Science, 2023)
Background Dogs present a significant opportunity for studies in comparative oncology. However, the study of cancer biology phenomena in canine cells is currently limited by restricted availability of validated antibody reagents and techniques. Here, we provide an initial characterization of the expression and activity of key components of the DNA Damage Response (DDR) in a panel of hematopoietic canine cancer cell lines, with the use of commercially available antibody reagents. Materials and methods The techniques used for this validation analysis were western blot, qPCR, and DNA combing assay. Results Substantial variations in both the basal expression (ATR, Claspin, Chk1, and Rad51) and agonist-induced activation (p-Chk1) of DDR components were observed in canine cancer cell lines. The expression was stronger in the CLBL-1 (B-cell lymphoma) and CLB70 (B-cell chronic lymphocytic leukemia) cell lines than in the GL-1 (B-cell leukemia) cell line, but the biological significance of these differences requires further investigation. We also validated methodologies for quantifying DNA replication dynamics in hematopoietic canine cancer cell lines, and found that the GL-1 cell line presented a higher replication fork speed than the CLBL-1 cell line, but that both showed a tendency to replication fork asymmetry. Conclusion These findings will inform future studies on cancer biology, which will facilitate progress in developing novel anticancer therapies for canine patients. They can also provide new knowledge in human oncology.